Influence of Freeze-Thaw Cycles on Mechanical Response of Levee Pavement. (27th January 2021) - Guo, Shuan; Lu, Zheng; Liu, Guokun; Zhuang, Baoli; Fan, Yongfeng; Zheng, Zuen
Abstract : The freeze-thaw cycles cause deterioration in mechanical properties of levee soil and further endanger the pavement structure on the embankment. This study attempts to comprehensively understand the mechanical response of pavement after freeze-thaw cycles. In this paper, the freeze-thaw cycles test under an open system was carried out, and then the triaxial compression test was conducted. Based on the test results, the effects of freeze-thaw cycles, temperature range, initial dry density, and initial moisture content of embankment soil on the mechanical response of road structure after freeze-thaw were calculated and analyzed. Finally, the stability of the slope of the levee was evaluated. The results show that the number of freeze-thaw cycles has the most significant impact on the mechanical response of pavement, the stress and strain of the structural layers vary in different ranges, and the pavement deflection increases by 5 times after 7 freeze-thaw cycles. However, the initial dry density and initial moisture content of the soil have little influence on the pavement structure, and the temperature range will exert an influence when it exceeds a certain threshold.